Examining the evidence that testing benefits subsequent information retrieval - Thinley Wangdi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the effect of frequent testing on students’ ability to retain the vocabulary and grammar materials learned in the classroom. A quasi-experimental research was employed, involving a sample of 50 Thai vocational students that was purposively recruited for this study. They were divided into two groups, each comprising 25 students. The experimental group received a test and corrective feedback after each unit of the course while the control group did not receive any unit test. The retention test scores were then compared to gauge the performance of the experimental and control groups. In doing this, the experimental group significantly outscored the control group in the retention test. The study found that frequent testing of the students in the course of their study had helped them retain vocabulary and grammar knowledge. The frequent testing may, therefore, be considered as one of the teaching methods to help students to have better retention of vocabulary and grammar knowledge.